Serving people with food allergies : kitchen management and menu creation - Schaefer, Joel J. (Hoboken, New Jersey : CRC Press, 2011)
An increasing number of people have food allergies or require special diets, and they are dining out more often. As a food service professional, how do you accommodate the needs of these customers? Serving People with Food Allergies: Kitchen Management and Menu Creation brings together a vast store of knowledge and practical advice for people working in the food service industry. This handy reference contains tools for cooks, managers, and chefs to help them create and modify recipes that meet the needs of people afflicted with multiple food allergies.
Chapter 1: Food Allergies and the Food Service Industry -- Chapter 2: Major Food Allergens Revealed -- Chapter 3: Food Allergen Summary -- Chapter 4: Special Diets The Real Life Experiences of Gina Clowes, Mom and President of AllergyMoms.com -- Chapter 5: Getting Started -- Chapter 6: Service Management -- Chapter 7: Kitchen Management -- Chapter 8: Menu Creation -- Chapter 9: Recipes for the Professional Kitchen
Includes index.
Keywords: FOOD ALLERGY DIET THERAPY